Redução do edema e da dor nos membros inferiores com caminhada e meia elástica - Carvalho, Carlos Alberto Martins (2018)
Chronic venous disease, with symptoms that lead to disability to work and loss of quality of life, affects millions of people worldwide. Objective: To evaluate the reduction of edema and pain in the lower limbs by walking while wearing elastic compression stockings. Patients and Methods: Twenty-one female patients with edema and pain of the lower limbs and with ages ranging between 32 and 72 years (mean = 49.5 years) were prospectively studied. Patients with signs and symptoms of chronic venous disease classified as C3 of the Clinical, Etiological, Anatomical, and Pathophysiological (CEAP) classification were included. All patients were evaluated by volumetry using the water displacement technique before and after each treatment session. Pain was analyzed using an analog pain scale that ranged from 0 to 10; where 0 indicated no pain and 10 the maximum bearable pain. Patients were randomized to use a stocking during the day; no stocking or walking on a treadmill for 50 minutes at 3 km/h in the evening. A 20/30 mmHg, knee-length elastic compression stocking was worn. The paired t-test and Wilcoxon test were used for data analysis. Results: The mean leg volume increased from 3041.42 mL in the morning to 3084.35 mL in the evening when no stocking was used during the day (p-value <0.0001). After walking on the treadmill, the volume dropped from 3099.17 mL to 3070.92 mL (p-value <0.001). On using compression stockings during the day, the initial mean volume of 3042.23 mL reduced to 3021.28 mL by the evening (p-value <0.0001). With regard to pain, there was a significant reduction after walking on a treadmill with elastic stockings (p-value <0.003). Stockings significantly reduced the pain during the course of the day (p-value <0.01). Elastic stockings donned in the evening were well tolerated, as they did not cause discomfort or allergic processes. Conclusions: Reductions in swelling and pain of the legs that develops over the course of the day can be reduced by using elastic stockings while walking on a treadmill in the evening.